Optimal Debt Policy Under Asymmetric Risk - Escolano, Julio (IMF Working Papers; Working Paper ;, 2016)
In the paper we show that, most of the time, smooth reduction in the debt ratio is optimal for tax-smoothing purposes when fiscal risks are asymmetric, with large debt-augmenting shocks more likely than commensurate debt reducing shocks. Asymmetric risks are a feature of 200 years of data for the U.S. and the U.K.: rare but recurrent large surges of the debt-to-GDP ratio, followed by very gradual but persistent declines over long periods. More informal evidence from many other countries suggests that asymmetry is a general feature of fiscal shocks. The gradual smooth reduction in the public debt to GDP ratio is not a response to past developments. Instead it is optimal given recurrent fiscal risks and the empirical characteristics of fiscal shocks. The behavior of the debt-to-GDP ratio in the U.K. and the U.S. seems roughly compatible with the prescriptions of the tax-smoothing model.